L’écart entre la théorie et la pratique : les protections en santé et en sécurité au travail et la réalité de la main-d’œuvre étrangère temporaire du domaine agricole en Ontario - Janet McLaughlin; Jenna Hennebry; Ted Haines (Perspectives Interdisciplinaires sur le Travail et la Santé)
Over 20,000 temporary foreign agricultural workers come to Ontario each year, primarily from Mexico and the Caribbean. Agricultural workers are exposed to a number of occupational health and safety (OHS) risks. This article discusses the various OHS protections available to workers and their limitations, and analyzes the specific challenges that temporary foreign workers face in accessing rights, such as language and cultural barriers, information gaps, and precarious employment and immigration status. It also analyzes the limitations with respect to OHS training and the provision and use of personal protective equipment, arguing that these protections are under-regulated and inconsistent. The article concludes with recommendations to improve shortcomings, including standardized and specific OHS training, random OHS inspections, and full inclusion of agricultural workers in provincial legislations. Findings are based primarily on interviews with 100 migrant farmworkers who reported injuries or illness, as well as with key stakeholders such as employers and government officials.